Genetic diversity analysis in the section Caulorrhizae (genus Arachis) using microsatellite markers - Palmieri, Darío Abel [UNESP]; Bechara, Marcelo D.; Curi, Rogerio Abdallah [UNESP]; Monteiro, Jomar P.; Valente, Sérgio E. S.; Gimenes, Marcos A.; Lopes, Catalina R. [UNESP] (Sociedade Brasileira de Genética, 2010)
Diversity in 26 microsatellite loci from section Caulorrhizae germplasm was evaluated by using 33 accessions of A. pintoi Krapov. & W.C. Gregory and ten accessions of Arachis repens Handro. Twenty loci proved to be polymorphic and a total of 196 alleles were detected with an average of 9.8 alleles per locus. The variability found in those loci was greater than the variability found using morphological characters, seed storage proteins and RAPD markers previously used in this germplasm. The high potential of these markers to detect species-specific alleles and discriminate among accessions was demonstrated. The set of microsatellite primer pairs developed by our group for A. pintoi are useful molecular tools for evaluating Section Caulorrhizae germplasm, as well as that of species belonging to other Arachis sections.
Keywords: Arachis; genetic diversity; germplasm; microsatellites; molecular markers